The effect of Pilates training on the severity and duration of dysmenorrheal pain and duration of bleeding in young girls - Mohamad Reza Ramezanpour; Malihe Kargozar (Mashhad University of Medical Sciences, 2018)
Introduction: Dysmenorrhea, as one of the most common gynecologic problems in women, is characterized by pain in the lower abdomen, which disrupts normal life. The aim of this study was to investigate the effects of Pilates training on the severity and duration of dysmenorrheal pain and duration of bleeding in young girls. Methods: Thirty young girls with the mean age of 22.21 ± 1.71 years, body mass index (BMI) of 23.89 ± 1.41 kg/m2 and fatigue score of 29.22 ± 3.71 were selected and randomly divided into two groups of Pilates training (n = 15) and control group (n = 15). At 24 hours before and 48 hours after the last exercise session, weight, BMI, fat percentage, severity and duration of dysmenorrheal pain and duration of bleeding were evaluated using McGill Pain Questionnaire and pain numerical rating scale. The experimental group performed the Pilates training protocol for eight weeks (three sessions per week). To analyze the data, independent t-test and Levene's test were run in SPSS, version 16. The significance level was set at P-value less than 0.05. Results: Weight, body fat percentage and BMI were not significantly different before and after eight weeks of Pilates training (P=0.06). In addition, there was no significant difference in the control group in this regard during this period (P=0.20). After eight weeks of Pilates training, a significant decrease in pain intensity scale was noted. After eight weeks of Pilates training, there was a significant difference in the intensity of pain (P=0.001) and duration of dysmenorrhea (P=0.019) between the training and control groups, but the duration of bleeding did not show a significant difference (P=0.893). Conclusion: The results of this study indicated that eight weeks of Pilates training could be useful in reducing pain intensity and duration of dysmenorrheal pain, while not affecting the duration of bleeding.